Design, Synthesis, Characterization, and Antitumor Activities of Benzimidazole-functionalized Organoruthenium Complexes Bearing Fluorine Group - Paşahan, Ramazan; Demirci, Özlem; Taşkin, Irmak İçen and Paşahan, Aziz and Sever, Meryem Rüveyda and Gök, Yetkin and Aktaş, Aydın (Medicinal Chemistry, 2025)
BackgroundThis work presents the synthesis of Ru(II)NHC complexes bearing a series of 4-fluorobenzyl group. These complexes have been characterized by a variety of spectroscopic methods (1H NMR, 13C NMR, and FTIR) and by elemental analysis techniques.MethodsThese complexes' antitumor activities against SH-SY5Y (human neuroblastoma) and HCT116 (human colon cancer) were investigated by 3-(4,5-dimethylthiazole-2-yl)-2,5-biphenyl tetrazolium bromide (MTT) assay.ResultsThe results showed that all the synthesized complexes exhibited significant cytotoxic effect with low IC50 values 15 ± 0.57, 15.26 ± 0.71, 7.64 ± 0.30, 27.66 ± 0.36 and 14.45 ± 0.84 (µg/mL) respectively.ConclusionFurthermore, apoptosis assessed by double labeling with Annexin V-FITC/PI indicated that complexes 1b and 1d can effectively induce apoptosis and inhibit cell proliferation at the S phase in SH-SY5Y cells. Taken together, Ru(II)NHC complexes containing the 4-fluorobenzyl group have significant potential for the development of novel, highly effective anticancer agents.
Keywords: benzimidazole